Application of Stochastic Flood Forecasting Model Using Regression Method for Kelantan Catchment - Osman S.; Aziz N.A.; Husaif N.; Sidek L.M.; Shakirah A.; Hanum F.; Basri H. (EDP Sciences, 2023)
Catchments; Disasters; Flood control; Floods; Land use; Least squares approximations; Offshore oil well production; Regression analysis; Rivers; Stochastic models; Stochastic systems; Storms; Watersheds; Flood forecasting; Flood forecasting models; Flood prone area; Least square principle; Mitigation measures; Natural disasters; Regression coefficient; Regression method; Weather forecasting